New Lipid Lowering Therapies for Cardiovascular and Metabolic Diseases: Lessons from the Past and Future Challenges - Bakillah, Ahmed (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book illustrates some of the most recent research efforts that have been made in lowering plasma cholesterol levels in patients with CVD. Selected articles aimed to illuminate advances and urgent challenges in the management of CVD, including disease management using statin-combined therapeutic strategies.